If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 7 = 9x + 15 Reorder the terms: 7 + 11x = 9x + 15 Reorder the terms: 7 + 11x = 15 + 9x Solving 7 + 11x = 15 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 7 + 11x + -9x = 15 + 9x + -9x Combine like terms: 11x + -9x = 2x 7 + 2x = 15 + 9x + -9x Combine like terms: 9x + -9x = 0 7 + 2x = 15 + 0 7 + 2x = 15 Add '-7' to each side of the equation. 7 + -7 + 2x = 15 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 15 + -7 2x = 15 + -7 Combine like terms: 15 + -7 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 4a+5b-2a= | | a+5b=-2 | | 6x+7=4x+5 | | 5*(x+3)= | | 2x-3y=-5 | | 5x=56-2x | | 3x+6x=63 | | 2x+3y=13 | | 2x+9=3x | | 3y*x+4=12y+4 | | 6x-5=3x+7 | | 62-2x=2x+14 | | -2-6x=14-8x | | 78-6x=9x+18 | | 10x+6=6x+22 | | 5x+10=73-2x | | 10*-27=73 | | 9+6x=64+x | | 4x+9=-33-10x | | 6x-2=16x-92 | | 5x+23=15x-57 | | 144-4x=4x+24 | | 11x-14=5x+4 | | 5x+47=8x+14 | | -12-2x=12-10x | | 52-4x=7x+19 | | 10x+7=7x+19 | | (n-5)*10=70 | | 4x+13=76-3x | | 6x-7=65 | | 8+4x=44+x | | (n-5)*5=25 |